2015
DOI: 10.1353/hsj.2015.0000
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Dialectics and Polemics: Canadian Catholic Schools Addressing LGBT Youth Issues

Abstract: In 2012, Canadian media coverage on Bill 13-an Ontario legislative proposal to require all publicly funded schools to support Gay-Straight Alliances as a means of addressing issues concerning bullied lesbian, gay, bisexual, and transgender (LGBT) students-instigated a divisive exchange among representatives of the Ontario Catholic school sector. Beyond these dialectics and polemics, a proactive mix of advocates from schools in the Waterloo Catholic District School Board (WCDSB) of Ontario took steady steps to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 45 publications
(60 reference statements)
0
22
0
1
Order By: Relevance
“…According to Mace et al (2016) school personnel are crucial in identifying LGBTQ victims of bullying, including cyberbullying, and helping students access support services within the school. School participants a study by Liboro et al (2015) were in agreement that the more confident and comfortable the teachers were in supporting LGBT students, the safer they felt. In addition, Duong and Bradshaw (2014) found that having an adult to talk to at school was protective against engaging in physical fights, attempting suicide, and making serious suicide attempts for cyberbullied sexual minority youth.…”
Section: School-focused Interventionsmentioning
confidence: 92%
“…According to Mace et al (2016) school personnel are crucial in identifying LGBTQ victims of bullying, including cyberbullying, and helping students access support services within the school. School participants a study by Liboro et al (2015) were in agreement that the more confident and comfortable the teachers were in supporting LGBT students, the safer they felt. In addition, Duong and Bradshaw (2014) found that having an adult to talk to at school was protective against engaging in physical fights, attempting suicide, and making serious suicide attempts for cyberbullied sexual minority youth.…”
Section: School-focused Interventionsmentioning
confidence: 92%
“…Supportive government and school board policies allowed for organizations (i.e., GSAs) to be accepted, subsequently fostering community connection and support for LGBTQ youth (Liboro et LGBTQ youth to feel supported in their wellbeing and safety. Additionally, a whole-school approach can support teachers and school administrators by providing them with more resources and external support, all instrumental to attain a whole-school system that is positive and inclusive (Liboro et al, 2015). GSAs may be an avenue whereby students can act to address anti-LGBTQ bias, to provide education, and address the silences on LGBTQ issues through whole school efforts (Liboro et LGBTQ youth, the scope of social support needs to be de ned to create a systemic framework that can map how different social support systems are associated with LGBTQ youth outcomes in school.…”
Section: Socio-political Values Of Wider Community Impacting School P...mentioning
confidence: 99%
“…Incorporating LGBTQ-inclusive curriculum and having access to LGBTQ-related information in schools was positively associated with perceptions of a safer school environment and negatively associated with perceptions of victimization(Snapp et al, 2015c;Toomey et al, 2012). Therefore, developing a curriculum that centers LGBTQ issues can disrupt homophobia, injustice, and other forms of oppression, which can provide safety and acceptance, and validate LGBTQ youths' experiences at school(Shelton & Lester, 2018;Wargo, 2019).Hidden, Heteronormative Curriculum Impedes LGBTQ Youth Support and EngagementThis theme expands parental resistance (Pearce & Cumming-Potvin, 2017), requiring the administration to provide the support needed for teachers to change the curriculum(Liboro et al, 2015). Note that the barriers may be contextual as high-stakes testing does not occur in all school contexts and curricula may be externallyconstructed in relation to the geographical context of the school environment.…”
mentioning
confidence: 99%
“…En el contexto de algunos países anglosajones y escandinavos, es posible reconocer un grupo de políticas de segunda generación, es decir, que avanzan más allá de las normativas de inclusión educativas y de educación sexual integral y ponen acento en la capacitación de docentes y directivos, por una parte, y en los contenidos curriculares, por otra. Existen naciones que han incorporado en su nomenclatura, a nivel del currículo o de documentos oficiales del sistema escolar, los conceptos de orientación sexual, expresión de género, identidad de género o identidades no binarias como reconocimiento de la diversidad sexual (Kjaran & Lehtonen, 2017;Larsson, 2014;Liboro et al, 2015). Un hito importante en este último tiempo es la decisión del gobierno escocés de enseñar de forma obligatoria la historia y los derechos del movimiento LGTB+ en las escuelas, como respuesta a la alta tasa de violencia y discriminación sufrida por adolescentes en el sistema escolar (Brooks, 2018).…”
Section: Las Políticas De Inclusión Lgtb+ En Las Agendas De Educaciónunclassified